PENGARUH ENTERPRISE RISK MANAGEMENT DISCLOSURE DAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Keuangan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia tahun 2017 – 2020) - Anindya Oryza Metana; Wahyu Meiranto (Diponegoro Journal of Accounting, 2023)
Banking is one of the business entities that acts as an economic source, besides that the banking sector is also one of the most dynamic sectors towards change, so it really needs accuracy and timeliness. Accuracy and timeliness are also needed by the company to meet the needs of stakeholders to increase the value of the company. This study aims to examine the effect of enterprise risk management disclosures and intellectual capital on firm value.The variables used in this study are firm value as the dependent variable and disclosure of enterprise risk management and intellectual capital as independent variables. The population in this study are financial companies in the banking sub-sector that are listed on the IDX in 2017-2020. Sampling in this study used a purposive sampling method with a sample of 140 observations from a total of 184 observations. The data used in this study is secondary data in the form of the company's annual report for the 2017-2020 period. The data analysis method used is multiple linear regression analysis.The results of this study indicate that the disclosure variables of enterprise risk management and intellectual capital have a significant effect on firm value.